Penerapan Self Assessment Pada Mata Kuliah Teknik Penulisan Laporan Kekaryaan Dan Seminar - Sukarni, Sri (Jurnal Ilmiah Mandala Education (JIME), 2022)
The Application of Self-Assessment on Artwork Report Writing Technique Subject. This study aimed to design self-assessment and to know the influence of the application of self-assessment on learning artwork report writing technique subject. The research method used experimental method with a quasi-experimental design. The data analysis used in this study was t-test analysis by Paired samples t-test model. As a result, the study showed that rubric was needed in designing self-assessment. The rubric consisted of eight components covered the parts of artwork report writing. Besides, the application of self-assessment can improve students’ learning outcomes on artwork report writing technique subject. It is proven by the average value of pre-test and post-test results. The results of pre-test obtained the average value was 72.00, while the results of post-test obtained the average value was 81.43 from the 7 samples of study. Data analysis by using paired samples t-test showed significance of sig 0.001 less than a significant level of 0.05 meaning that there was a positive influence on the application of self-assessment on learning artwork report writing technique subject.